In-vitro assessment of first-line antifungal drugs against Aspergillus spp. caused human keratomycoses - Anamangadan Shafeeq Hassan; Annanthode Balakrishnan Sangeetha; Coimbatore Subramanian Shobana; Arumugam Mythili; Sreeram Suresh; Baskaran Abirami; Raed Abdullah Alharbi; Saleh Abdullah Aloyuni; Ahmed Abdel-hadi; Mohamed F. Awad; Randa Mohamed Ismail; Kanesan Panneer Selvam; et al. (Elsevier, 2020)
Background and objectives: Aspergillus keratitis are in the increasing trend and reported as the second most common cause of mycotic keratitis in developing countries. The present study was designed to isolate, identify Aspergillus spp. from the keratits/corneal ulcer patients attending a tertiary care eye hospital, Coimbatore, South India and to assess the minimum inhibitory concentrations (MICs) against ten clinically used first-line antifungal drugs. Methods: A total of seventy-three Aspergillus strains isolated from corneal scrapings were included and assessed for a period of one year. All isolates were identified up to the species level by morphological observations. Antifungal drug susceptibilities were determined against a standard panel of antifungal agents. Conclusions: Five different species of aspergilli, A. flavus (n=53), A. fumigatus (n=14), A. terreus (n=9), A. tamarii (n=6) and A. niger (n=3) were identified based on morphological features. Minimum inhibitory concentration analyses indicated that, voriconazole, natamycin, itraconazole, clotrimazole, econazole followed by ketoconazole shall be the order of choices for the effective treatment for Aspergillus keratitis.